2017
DOI: 10.1093/annweh/wxx097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fire Suit Ensembles on Firefighter PAH Exposures as Assessed by Skin Deposition and Urinary Biomarkers

Abstract: Over the past 10 years, a number of safety measures for reducing firefighters' exposure to combustion particles have been introduced in Sweden. The most important measure was the reduction in the time firefighters wear suits and handle contaminated equipment after turn-outs involving smoke diving. This study was divided into two parts, those being to investigate the level of protection obtained by multiple garment layers and to assess exposure during a standardized smoke diving exercise. First, realistic work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
(46 reference statements)
2
40
0
Order By: Relevance
“…The ability of turnout gear to attenuate PAHs and other combustion byproducts from contacting skin may depend on many factors including physical state (particulate vs. vapors) and concentrations of the airborne chemicals, as well as the properties of the turnout gear (e.g., permeability and tightness of interfaces). Wingfors et al [15] reported higher turnout gear/station gear workplace protection factors (WPFs) for total PAHs (WPF = 146) than naphthalene (WPF = 49), the most volatile PAH that exists predominantly in gas phase during firefighting. In a previous publication, our group reported median personal air concentrations of benzene for the attack and search firefighters of 40 and 38 ppm, respectively [5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of turnout gear to attenuate PAHs and other combustion byproducts from contacting skin may depend on many factors including physical state (particulate vs. vapors) and concentrations of the airborne chemicals, as well as the properties of the turnout gear (e.g., permeability and tightness of interfaces). Wingfors et al [15] reported higher turnout gear/station gear workplace protection factors (WPFs) for total PAHs (WPF = 146) than naphthalene (WPF = 49), the most volatile PAH that exists predominantly in gas phase during firefighting. In a previous publication, our group reported median personal air concentrations of benzene for the attack and search firefighters of 40 and 38 ppm, respectively [5].…”
Section: Discussionmentioning
confidence: 99%
“…The PAH metabolites were measured using an enzyme-linked immunosorbent assay (ELISA), which is not specific, but correlates well (r = 0.89) with the sum of metabolites of four PAHs (naphthalene, fluorene, phenanthrene, and pyrene) measured by gas chromatography-mass spectrometry in exposed workers' urine [34]. Other studies of firefighters have documented post-fire increases in metabolites of phenanthrene, fluorene, and pyrene [15,16].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations